Comprehensive effects of heat and flow on the methane hydrate dissociation in porous media. (15th February 2023) - Zhang, Zhaobin; Xu, Tao; Li, Shouding; Li, Xiao; Briceño Montilla, Maryelin Josefina; Lu, Cheng
Abstract: The dissociation of methane hydrate in porous media is a heat flow coupling process. In this paper, we established a heat flow coupling algorithm for hydrate dissociation. A core-scale hydrate dissociation model was established and was verified against a laboratory dissociation experiment. The evolutions of the key characteristics, such as the temperature, the energy, and the hydrate/ice saturations, were analyzed. The effects of heat conductivity and permeability on dissociation characteristics and gas production rate were studied. It is found that there are three different modes under the coordinate system of heat conductivity and the permeability of porous media. In the flow-controlling mode, the rate of hydrate dissociation is mainly related to the flow resistance. In the heat-controlling mode, the rate of hydrate dissociation is mainly related to heat supply. In the heat flow-coupling mode, both the increase in the permeability and the heat supply have positive effects on the increase in the hydrate dissociation rate. In addition, there are different hydrate dissociation front expanding characteristics for the different modes. This analysis of the dissociation mode improves the understanding of events associated with the hydrate dissociation process. Highlights: A thermal flow coupling algorithm for hydrate dissociation was proposed and was verified by experimental data. The comprehensive effects of heat and flow on hydrate dissociation were investigated. Three hydrate dissociation modes were found with the change of permeability and heat conductivity.